STIGMA DAN PENERIMAAN SOSIAL TERHADAP ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH INKLUSI: ANALISIS LITERATUR - Nurul Harizah; Nasyita; Verawati; Nurhasanah; Hasmiati; Muh. Kadir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Stigma and low social acceptance toward children with special needs remain major challenges in inclusive education. These conditions may hinder students’ social interaction, learning participation, and their academic and emotional development. This study aims to analyze previous research findings regarding forms of stigma, levels of social acceptance, influencing factors, and strategies to create a more inclusive school environment for children with special needs. The study employs a qualitative descriptive approach using a literature review method by analyzing relevant journal articles, books, and educational documents. The results indicate that stigma toward children with special needs is commonly manifested through negative labeling, stereotyping, discrimination, and social exclusion. Conversely, positive social acceptance is influenced by knowledge, attitudes, interaction experiences, school support, and the development of an inclusive culture. These findings emphasize the importance of strengthening inclusive values, increasing awareness within school communities, and promoting collaboration among teachers, students, and parents to enhance social acceptance in inclusive schools.